The State of E-Business in Slovenian Public Administration: The Case of Administrative Units - Mitja Jelenič; Mirko Vintar (Central European Public Administration Review)
Over the last few years e-government in Slovenia has experienced very rapid development, with the latest EU surveys showing that Slovenia is among the most advanced member states in this field. However, the actual use of public e-services lags far behind the growing supply. This paper offers a comparative analysis of the current state of affairs in this field in Slovenia, focusing on the country’s administrative units. That analysis is based on the results of empirical research into the administrative units’ e-business, which was carried out in the first half of 2009 by the Institute for Public Administration Informatisation at the Faculty of Administration. The research looked at e-business in the most typical areas of the administrative units’ work, such as internal affairs, the environment and physical planning, agriculture etc., which most accurately reveal the current state of e-business in Slovenia’s public administration, particularly insofar as it relates to operations with citizens. The paper also examines the e-business of administrative units in their internal operations and in operations with other administrative bodies. The final part includes a comparison of the results of the empirical research with the latest results from the EU Capgemini Benchmark study (Capgemini, 2009), as well as a number of other international studies.